Dr. Vasantrao Gowarikar - An Educationalist - ., . (Journal of Engineering Education Transformations, 1995)
Dr. Vasant Cowariker obtained his M.Sc. and Ph.D. in Chemical Engineering from the University of Birmingham, England; worked for 5 years with the U.K. Atomic Energy Authority and Summerfield Research Station, Kidderminister, Worcestershire as Senior Technical Officer; joined the space centre at Thumba (Kerala, India) in 1967 as Head of Propellant Engineering Division; became the Director of the Chemicals and Materials Croup and finally rose to head the Vikram Sarabhai Space Centre (VSSC), Indian Space Research Organisation’s (ISRO) largest establishment entrusted with the responsibility of development of advanced rockets and launch vehicles for India’s space programme.